Rapid callogenesis and plant regeneration from nodal explants of Sida cordifolia L.- an important medicinal plant - Pattar, Pramod V; Jayaraj, M (Journal of Phytology, 2012)
An efficient reproducible protocol for rapid callus induction and plant regeneration from young nodal explants of Sida cordifolia L. was developed. High frequency of green, compact organogenic callus was obtained from nodal explants cultured on MS medium supplemented with 0.5 mg/L Kinetin individually and combination with 0.5 mg/L NAA and successful plant regeneration from in vitro derived callus of Sida cordifolia L. Kn and BAP individually and in combinations with NAA and IAA used for regeneration of plantlets from callus culture. Maximum number of multiple shoots were developed on MS medium supplemented with 0.5 mg/L KN+0.5 mg/L NAA. All the in vitro shoots were then transferred to rooting medium supplemented with different concentrations of 0.2-1.0 mg/L NAA and IAA individually. The best rooting response was observed on 0.8 mg/L NAA. The well rooted plantlets were transferred to polybags containing soil + sand + vermiculites (2:1:1) for hardening. Finally the hardened plantlets were transferred to fields for acclimatization.